Pengaruh Pendidikan Orang Tua terhadap Sikap Disiplin Tata Tertib Siswa Kelas VI di SD Negeri 24 Banda Aceh - Sahnaz Marlianda; Ahadin Ahadin; Said Darnius (Universitas Syiah Kuala, 2023)
Education is a shared responsibility, namely family, community and school. The family is a child's first educational institution. Parents play an important role in shaping their children, including developing a disciplined attitude. This study is entitled,